-2(x+1)-3=9

Simple and best practice solution for -2(x+1)-3=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+1)-3=9 equation:


Simplifying
-2(x + 1) + -3 = 9

Reorder the terms:
-2(1 + x) + -3 = 9
(1 * -2 + x * -2) + -3 = 9
(-2 + -2x) + -3 = 9

Reorder the terms:
-2 + -3 + -2x = 9

Combine like terms: -2 + -3 = -5
-5 + -2x = 9

Solving
-5 + -2x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -2x = 9 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = 9 + 5
-2x = 9 + 5

Combine like terms: 9 + 5 = 14
-2x = 14

Divide each side by '-2'.
x = -7

Simplifying
x = -7

See similar equations:

| 4(3-x)=16 | | 2.6a-5=-2.4 | | 20-y-y^2=0 | | h-23=7 | | 5y-x=25 | | 7x-5=-6x+3 | | t^2-t-6=0 | | 7x-5=-6+3 | | 7x-5=-6x+5 | | 5x^3-29x^2+55x-28=0 | | X^2+7X-2.25=0 | | 5(4x)+1=45 | | 18y-10=2+18y | | 1x+2y=3z | | (x-3)*3(x+1)=3(2x-1) | | 4y+2y=5y | | (x-3)*3(x+1)-3(2x-1)=0 | | z^3-7z^2+6=0 | | 3x+14=49-2 | | 2a^2+13a+6=0 | | 57-2x=7x+22 | | 8-7x=77-28x | | 4x+12=3x-6+4x | | 7Y+11=17 | | 1/2-x+7=3/4+2x | | 76=38(r) | | 4y+2y=5y+7 | | r+2.1=6.1 | | x+10+2x+7=9x+9 | | 3(5m-6)-28= | | (3/4)(2x+1)=2 | | 4+14s-2=7s+74-5s |

Equations solver categories